Verantwoording in de schaduw van de macht. Horizontale verantwoording bij zelfstandige uitvoeringsorganisaties - Schillemans, T. (Lemma, 2007)
In the Netherlands, as in other OECD-countries, many executive agencies have been granted substantial autonomy in recent years. Central to agentification is that governmental organizations are placed more or less outside of departmental hierarchies. From the outset, the establishment of agencies has induced height-ened political and academic concern regarding their accountability. This is be-cause their partial separation from their parent departments also cuts through the customary mechanisms for accountability. In the Netherlands in particular, but also in other countries, many authors have proclaimed that 'horizontal accountability' is a promising solution for the ac-countability-problems of agencies. The concept broadly focuses upon forms of accountability that address other stakeholders and demands besides those of the hierarchical principal. The research in this book addresses three conceptual and three empirical issues. The first conceptual issue is to develop a suitable conception of horizontal ac-countability. The second conceptual issue is to arrive at a fuller understanding of the accountability problems of executive agencies. The third and most difficult question is to draft a normative framework from which empirical practices of horizontal accountability can be evaluated. The empirical contribution of the research focuses upon three issues. The first issue is to identify which arrangements for horizontal accountability actually exist. The second empirical issue is to study how a number of cases of horizon-tal accountability operate in practice. The third empirical question is to evaluate this from the developed normative framework. This book is based upon research conducted into thirteen arrangements for hori-zontal accountability of six agencies. In addition, the arrangements of seven other agencies were studied In the literature, accountability arrangements have been categorized on different grounds. The point of departure for the notion of horizontal accountability is the hierarchical relationship between actor and forum. In order to be categorized as a case of horizontal accountability, the forum needs to be independent from both the agent and the principal, and is not hierarchically superior to the agent. In this research, arrangements for horizontal accountability have been identified for 82 Dutch executive agencies. A substantial minority of these 82 agencies account for their behaviour through one or more arrangements for horizontal accountability. In total 60 arrangements were found. They can be found primarily within large autonomous administra-tive authorities. In total there are 14 boards, 15 client councils, 5 boards of ex-perts, 11 independent evaluation committees ('visitation') and 14 internal om-budsmen. The arrangements for horizontal accountability have been evaluated from a de-mocratic perspective and a cybernetic (learning) perspective. This results in the unambiguous conclusion that, from a cybernetic perspective, all arrangements render many (albeit modest) positive contributions. From a democratic perspec-tive however, horizontal accountability provides little added value. The general conclusion of this research is that the arrangements for horizontal accountability operate in a way that clearly corresponds with the cybernetic tradition and has little added value from the democratic perspective. The most captivating finding of this research is that hierarchical accountability strongly influences processes of horizontal accountability. Horizontal account-ability operates in the 'shadow of hierarchy'.
Keywords: Social Sciences; horizontal accountability; accountability; agencies; democracy; learning perspective; executive agencies; boards; evaluation; client councils